Smart Nanomaterials for Treatment of Biofilm in Orthopedic Implants - Hong, Qimin; Huo, Shicheng; Tang, Haozheng; Qu, Xinhua; Yue, Bing (Frontiers in Bioengineering and Biotechnology, 2021)
Biofilms refer to complex bacterial communities that is attached to the surface of animate or inanimate objects, which highly resist the antibiotics or the host immune defense mechanisms. Pathogenic biofilms in medicine are general, chronic, and even costly, especially on medical devices and orthopedic implants. Bacteria within biofilms are the cause of many persistent infections, which are almost impossible to eradicate. Though some progress has made in comprehending the mechanisms of biofilm formation and persistence, novel alternative compounds or strategies and effective anti-biofilm antibiotics are still lacking. Smart materials with nano size which are able to respond to external stimulus or internal environment have a great range of applications in clinic. Recently, smart nanomaterials with or without carriage of antibiotics, targeting specific bacteria and biofilm properties under the condition of some stimulus, have shown great potential for pathogenic biofilm and resident bacteria eradication. This review summarizes and describes biofilm formation process, as well as some of current treatment approaches in the realm of biofilm probably involving orthopedic implants. Finally, some outstanding challenges and limitations that need to be settled urgently in order to make smart nanomaterials effectively target and treat implant biofilms are also discussed. It is hoped that there will be more novel sterilization strategy for biofilm infection in the prospective future.